(untitled) (Bangladesh Agronomy Journal, 2020)
Short-statured and lodging resistant rice plants with long to medium slender grain are the expected criteria for aromatic rice. However, most of the aromatic rice varieties in Bangladesh do not meet the expected criteria. Therefore, this study was undertaken to detect short-statured rice plants with aromatic and long to medium slender grain where twelve advanced rice lines (derived from the local rice germplasm) with a local check Kataribhog were evaluated. All the genotypes demonstrated significant variation for different parameters such as plant height at harvest, yield per hectare, grain length, grain size, grain shape, and aroma. At harvest, the shortest plant height was obtained from SAU ADL11 (107.09cm), and it was statistically similar to SAU ADL4 (111.68cm) and SAU ADL5 (111.89cm). However, the plant height of check variety Kataribhog was 167.17cm. The highest grain yield per hectare was found in SAU ADL5 (4.79 tha-1), where it was 2.71 tha-1 in Kataribhog. Besides, the grain yield of shorter genotypes SAU ADL4 and SAU ADL11 was 3.47 t ha-1 and 3.84 t ha-1 , respectively. The SAU ADL1 provided the highest kernel length (7.31mm), and the lowest kernel length (4.87 mm) was recorded in the check. Kernel length of short-statured genotypes ranged from 7.01 mm to 6.57 mm. Kernel size of all evaluated genotypes was long to medium; whereas, it was short for Kataribhog. Kernel shape of these short-statured genotypes was slender to medium. In case of aroma, SAU ADL3, SAU ADL5, SAU ADL7, SAU ADL9, SAU ADL10, and SAU ADL11 were moderately aromatic, and other genotypes were non-aromatic. However, Kataribhog was strongly aromatic. Finally, SAU ADL5 and SAU ADL11 were evaluated as important germplasms in respect of different characters such as shortstatured plant, long to medium slender grain, and aroma. These two lines could be potential inbreed aromatic rice genotypes for Bangladesh. Bangladesh Agron. J. 2019, 22(2): 91-102